Spatial distribution characteristics and influencing factors of organic carbon in sediments of Tongshun River riparian zone. (August 2020) - Ma, Yueyong; Wang, Zhiqiang; Ma, Teng; Chen, Shuxian
Abstract: The riparian zone is closely related to the surrounding environment, and it is important to find out the distribution characteristics of organic carbon in the sediment of the riparian zone. In this paper, the distribution of organic carbon in sediments and its influencing factors were analyzed in the riparian zone of small watershed. The results show that the distribution of organic carbon was significantly related to the lithology of sediment, and the sedimentary environment determined the content of organic carbon in sediment. In shallow sediments, organic carbon changed significantly with depth, and redox conditions were the main influencing factors. When the environment changed from oxidation condition to reduction condition, both the mineralization of organic carbon and the change of iron oxide morphology would change the stabilizing effect of organic carbon, thus affecting the distribution of organic carbon. In addition, under the influence of flood, the organic carbon in the riparian sediments changed with the distance to the river in the horizontal direction. Highlights: Distribution of organic carbon in deep sediments was emphasized. Explored the influences of sediments in riparian zone by flooding. Spatial distribution of organic carbon in sedimentary was studied comprehensively. The sedimentary environment determined the content of organic carbon in sediment. Eh would affect The mineralization of organic carbon and the morphology of iron oxides.